MORPHOLOGICAL SPECIES VARIABILITY IN THE STEM-BORER GENUS Sdrpophaga, (LEPIDOPTERA: PYRALlDAE) ON GRAMINEOUS CROPS - Mohamad Amir; Arifin Katohardjono; Sri Suharsini Siwi; Rosichon Ubaidillah (Treubia, 2004)
The objective of this study is to observe variations between and within species using morphometry. Collections of Scirpophaga were carried out at rice fields in the Northern Coastal area of Java (Pantura): Kerawang, Cikampek, lndramayu, Cirebon, at sugar-cane plantations in Yogyakarta and Pasuruan and various gramineous crops in areas of South Bandung and Lampung from March 1998 to March 1999. Identification was done using morphology of adult characters. Variation within the population groups are recognized by taking measurement of parts of the head, for example measurement of the length and width of the head. Other characters used ill keying adult Lepidoptera to family are those of willg uenation. Also the morphology of male genitalia were used as main characters to differentiate species Results from this studies shown that: a) Scirpophaga innotata. Measllrement of parts of the head from sample collected showed very little variation, ihier were mentioned as a group. Variation based on wing size, length and width of forewing can be divided into two groups sizes; the large group size (950 - 1025 lI11n/100) and the smolt group size (850 - 860min/100). Variation based on the size of male gellitalia were more varied in ranging; between 20 - 26min/100 in length and 23 - 35 min/100 but they can be put into one group. b) Scirpophaga incertulas. Measurelllent of parts of the head show little variation in the scattered diagram distribution, and is considered as the same population group. Variation based on wing size, length and width of forewing collected from various places in Java indicated that populations of this insect does not indicate any differences in term of types of wing uenations and considered as similar populatious. Variation based on the size of male genitalia seemed to the same group in the scattered diagmm. c) Scirpophaga excerptalis Measurement of parts of the head (the length and width of the head) considerd as one population. Variation based on the size of nutle genitalia seemed to the smile group in the scattered diagrmn.